Atoms and Radiation - Jean Dalibard (Collège de France, 2015)
Light and matter are very closely linked in our modelling of the physical world. From the formulation of quantum theory to the invention of laser, the interaction between atoms and radiation has played a crucial role in the development of today's science and technology. By controlling this interaction, the lowest temperatures ever recorded are now reached. Cooling atomic gases with laser light produces "quantum matter" with radically different properties from those of ordinary fluids. These c...